Students’ Misconceptions in Psychology: How You Ask Matters…Sometimes - Annette Taylor; Patricia Kowalski (Journal of the Scholarship of Teaching and Learning, 2012)
Misconceptions about psychology are prevalent among introductory students. Just how prevalent and what can be done to change these misconceptions depends on valid methods of assessment. The most common method of assessment, the true/false questionnaire, is problematic.  The present study compared true/false with forced choice formats to determine whether the formats give different estimates of student misconceptions. Introductory psychology students (N = 165) answered 39 misconceptions in both the true/false and forced choice formats.  Students differed in accuracy when assessed with the different formats, with 33.05% accuracy for true/false and 41.29% accuracy for forced choice.  In the analyses of individual items we observed that some items did not differ in level of accuracy across formats and other items did differ.  We conclude that the true/false method of assessing misconceptions may overestimate students’ level of misconception and recommend continued attention to how researchers assess misconceptions.